Pengaruh Keterlibatan Konsunen, Perbedaan Persepsi Merk, Karakteristik Hedonis dan Kebutuhan Mencari Variasi terhadap Keputusan Perpindahan Merk Telepon Selular - Basuki Nugroho; Magdalena Nany (Fakultas Bisnis UKDW, 2007)
The tight global competition had enforced marketers to focus on brand loyalty, so as to reduce brand switching. Therefore, studies focus on customer loyalty; customer purchasing power and customer satisfaction are growing rapidly.The objective of this research was to provide empirical evidence obout the effects of customer involvement, difference of brand perception, hedonism characteristic and variation seeker on brand switching decision both partially and simultaneously. Using the multiple regression analysis, the results showthat customer involvement, difference of brand perception and variation seeker partially has significant effect on brand switching decision. However, hedonism characteristic has insignificant effect on brand switching decision.The result also shows that customer involvement, dffirence of brand perception, hedonism characteristic and variation seeker simultaneously has significant effect on brand switching decision.Keywords: brand loyalty, customer involvement, difference of brand perception, hedonism charact eris tic, v ariation s eeker, brand switching decision